PENDIDIKAN KARAKTER BERDASARKAN NILAI-NILAI PENDIDIKAN URSULIN - Krismawan, Daniel Febri; Widiatna, Alexius Dwi (CREDENDUM: Jurnal Pendidikan Agama, 2020)
This research focuses on character education through values of Ursuline education at Santo Bernardus Madiun Junior High School. This research was conducted at Santo Bernardus Madiun Junior High School because it is an Ursuline school which is cared for by Ursuline nuns who have typical Ursuline educational values. The aim of this research is to explore the efforts made by the school about character education through values of Ursuline education. This research is a qualitative descriptive research with a case study method using data triangulation techniques. Determining informants in this research uses techniques purposive sampling. Data was collected through observation, interviews and documentation. Data were analyzed using the steps of data collection, data condensation, data presentation, and drawing conclusions. Data validity checking techniques use source triangulation and technical triangulation. The results of this research are: (1) Character education in Ursuline Educational Values is implemented through school programs, learning activities, foundation support, awareness of educators and education staff, student awareness. Routine implementation activities are carried out every day by morning prayers and meditation. Apart from that, it is provided through school pastoral activities. (2) The values of Ursuline education are a concrete manifestation of Serviam's motto which is characteristic Ursuline school. Serviam's motto is expressed in the Ursuline educational values that are lived, namely: Love and Compassion, Integrity, Courage and Toughness, Unity, Totality, and Service in accordance with the spirit of Saint Angela.